Small‐bowel dislocation during long‐term MRI observation – insights in intestinal physiology. (12th January 2014) - Bickelhaupt, Sebastian; Froehlich, Johannes M.; Wentz, Klaus‐Ulrich; von Weymarn, Constantin; Patak, Michael A.
Summary Magnetic resonance imaging (MRI) of the abdomen is a widely established imaging modality in the diagnostic workup of patients suffering from abdominal disorders. Small‐bowel motility analyses using MRI have recently been introduced to provide functional information about the intestine not provided by morphological analyses. This is of clinical importance as motility disorders correlate with inflammation. Yet motility analyses mainly rely on a series of acquisitions in coronal orientation. Temporal displacement of small‐bowel loops out of the coronal slice could falsify qualitative and quantitative motility analyses. Thus, our study quantified three‐dimensional (3D) dislocation of small‐bowel loops during abdominal MRI examinations with the patient lying in prone position to investigate its influence on motility analyses. Our study revealed segmental small‐bowel displacement during MRI examinations in prone position to predominantly occur in craniocaudal orientation and in a smaller extent in lateral and ventrodorsal orientation. However, the displacement amplitudes are rather small and might not significantly influence small‐bowel motility analyses in 2D coronal plane in general.